The Role of Supplementary Food Consumption on The Nutritional Status of Pregnant Women and Toddlers in Tuban, Indonesia - Nur Maziyah Hurin'in; Tri Yunita Fitria Damayanti; Nur Cholila; Saliya; Sri Setyowati (Journal of Community Medicine and Public Health Research, 2026)
Pregnant women with chronic energy shortage face an elevated risk of sudden maternal mortality during the perinatal period and the likelihood of delivering infants with low birth weight, who may subsequently encounter growth issues in early childhood. This study aimed to examine the relationship between extra feeding and the nutritional status of pregnant women and children. This was a cross-sectional correlational analytical design. The study population comprised pregnant mothers and children registered at two designated health centers in Tuban. The health center was selected based on local health data indicating a high prevalence of undernutrition among toddlers and chronic energy insufficiency among pregnant women. The sample was drawn using purposive sampling methods grounded in specific inclusion and exclusion criteria. The group consisted entirely of pregnant women suffering from chronic energy shortage. The study sample comprised 30 pregnant women with chronic energy deficit. The population of the Local Supplementary Feeding (PMT) Lokal program consisted entirely of undernourished toddlers. The sample comprised 86 malnourished babies from the vicinity of the Wire Health Center. Data analysis will be conducted at a significance level of 0.05, using Spearman's rank correlation and the contingency coefficient. This study identified a strong association (p=0.010) between pregnant women’s adherence to supplementary feeding programs and increased upper arm circumference. A strong connection (p=0.000) was identified between the provision of supplemental meals to undernourished toddlers and their nutritional status. Supplementary food shows a minimal association with improved nutritional status in undernourished toddlers and pregnant women, as indicated by increased upper-arm circumference among those with chronic energy shortage. Researchers will conduct further studies to identify the underlying cause of the supplementary meal program's inefficacy in improving nutritional status over the three months.